Health Counseling about Exclusive Breastfeeding to Improve Breastfeeding Success and Improve Infant Health Level - Riza Tsalatsatul Mufida; Risa Maya Sardewi; Atik Fitrian Diyanti; Dewi Asrifatul Ulya; Lely Dian Agustina; Indriani Agustin; Euis Niawati (Universitas STRADA Indonesia, 2025)
One of the main causes of low exclusive breastfeeding is the lack of knowledge of mothers about the benefits of exclusive breastfeeding. Many mothers do not fully understand the importance of exclusive breastfeeding and prefer to give formula milk, even though exclusive breastfeeding is the best choice for babies. Not a few mothers also find it difficult to provide exclusive breastfeeding, either because of medical problems, work, or ignorance about the right way to breastfeed. The aim of this community service is to optimize breastfeeding knowledge about exclusive breastfeeding to increase the success of breastfeeding and improve the baby's health status. This activity was carried out by providing counseling on exclusive breastfeeding by providing a Pre-Test before being given counseling and a post-test after being given counseling. Then conducting a demonstration of how to breastfeed properly and correctly. This counseling was carried out at the Al Kautsar Clinic, Setro Village, Prambon Sidoarjo which was attended by 20 breastfeeding mothers. The results before being given counseling were 8 participants (40%) with Good knowledge and after the activity there was an increase to 15 participants (75%) with Good knowledge. It is hoped that more emphasis will be placed on providing exclusive breastfeeding to increase the success of breastfeeding and improve the health of babies.